2021
DOI: 10.1016/j.ymthe.2021.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Pre-conditioning modifies the TME to enhance solid tumor CAR T cell efficacy and endogenous protective immunity

Abstract: Chimeric antigen receptor (CAR) T cell therapy has led to impressive clinical responses in patients with hematological malignancies; however, its effectiveness in patients with solid tumors has been limited. While CAR T cells for the treatment of advanced prostate and pancreas cancer, including those targeting prostate stem cell antigen (PSCA), are being clinically evaluated and are anticipated to show bioactivity, their safety and the impact of the immunosuppressive tumor microenvironment (TME) have not been … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 57 publications
0
39
0
Order By: Relevance
“…The potential contribution of the host immune system in the effect of CAR T cells has been shown in preclinical (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) and clinical (43)(44)(45) studies. Recent studies indicate that immunogenic cell death eliciting endogenous cells responses contribute to the effects of adoptively transferred immune effector cells, including TCR-transgenic T cells (46,47), NK cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…The potential contribution of the host immune system in the effect of CAR T cells has been shown in preclinical (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) and clinical (43)(44)(45) studies. Recent studies indicate that immunogenic cell death eliciting endogenous cells responses contribute to the effects of adoptively transferred immune effector cells, including TCR-transgenic T cells (46,47), NK cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies of solid extracranial cancers have shown that strategic timing of chemotherapy and immunotherapy can achieve synergies that are significantly greater than either individual approach 3 8 . In addition to reducing tumor mass, thereby reverting T cell exclusion and promoting T cell infiltration 9 , chemotherapy can also generate pro-inflammatory T cell and myeloid cytokine expression 10 . Alkylating agents such as Temozolomide (TMZ), the primary chemotherapeutic agent for glioblastoma (GBM), methylates the O 6 position of guanine residues thereby inducing mispairing with thymine during replication inducing cascading cycles of thymine excision and reinsertion, DNA strand breaks, and activation of the DNA damage response leading to cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that conditioning chemotherapy, commonly referred to as "lymphodepletion", plays a critical role in modulating the TME for CAR T cell effect. In particular, cyclophosphamide administration increased intra-tumoral PSCA-targeted CAR T cell accumulation and expansion in vivo (38). Gene ontology enrichment analysis identified T cell migration and IFN-γ production as key processes enhanced by cyclophosphamide pre-treatment.…”
Section: Car-t Cell Therapy In Mcrpcmentioning
confidence: 96%